2004
DOI: 10.1007/s11284-004-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the distribution of two co‐occurring dwarf bamboo species (Sasa kurilensis and S. senanensis) in a conifer‐broadleaved mixed stand in northern Hokkaido

Abstract: Factors influencing the distribution of two co-occurring dwarf bamboo species (Sasa kurilensis and S. senanensis) in a conifer-broadleaved mixed stand in northern Hokkaido Abstract We have investigated the factors influencing the distribution of co-occurring two dwarf bamboo species, Sasa kurilensis (Ruprecht) Makino et Shibata and S. senanensis (Franchet et Savatier) Rehder, within a conifer-broadleaved mixed stand managed with selection cutting in northern Japan. We first sought the possible determinant fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 20 publications
(20 reference statements)
3
33
0
Order By: Relevance
“…Previous studies have shown that Abies regeneration rates are higher on south-facing slopes (Yamamoto et al, 1995) where there is typically a higher heat load index (Hosaka et al, 2008). These factors may have no relevance to the distribution of dwarf bamboo, as they are not significant determinants of culm density (Noguchi and Yoshida, 2005). Local topography may be indirectly associated with the pathogenic fungus Racodium therryanum (or Herpotrichia juniperi ), which is another significant factor inhibiting natural regeneration in Hokkaido (Cheng and Igarashi, 1990).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have shown that Abies regeneration rates are higher on south-facing slopes (Yamamoto et al, 1995) where there is typically a higher heat load index (Hosaka et al, 2008). These factors may have no relevance to the distribution of dwarf bamboo, as they are not significant determinants of culm density (Noguchi and Yoshida, 2005). Local topography may be indirectly associated with the pathogenic fungus Racodium therryanum (or Herpotrichia juniperi ), which is another significant factor inhibiting natural regeneration in Hokkaido (Cheng and Igarashi, 1990).…”
Section: Discussionmentioning
confidence: 95%
“…Because dwarf bamboo negatively affects the density of Abies seedlings in selection forests (Hosaka et al, 2008;Nakagawa and Kurahashi, 2005;Noguchi and Yoshida, 2005), shading from overstory trees most likely led to increased abundance of Abies juveniles. Slope angle is also correlated with the density of dwarf bamboo undergrowth, which significantly decreases on a steep slope (Noguchi and Yoshida, 2005;Hosaka et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The volume of understory vegetation was also more abundant in the managed stands. The quantity of dwarf bamboo, a dominant understory species in the study site, often correlates negatively with the volume of overstory trees [30], and rises after disturbance. Nonetheless, the overall difference between stands was small, and there was no significant difference in species diversity among understory vegetation (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…Phyllostachys bambusoides f. shouzhu Yi is a bamboo species belonged to Bambusoideae of Gramineae [1,2], and mainly distributed in Sichuan and Chongqing, Southwest China [3]. As its bigger diameter at breast height (DBH)(up to 13cm) and its longer internode (up to 60 cm), the species is planted on a commercial scale for the large culms, and are widely used for building materials, farm tools, and furniture and are also split for weaving various bamboo articles.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the morphological features and biomass is necessary for estimating the bamboo productive forces and improving the silvicultural level, and its result may be used in guiding the forestation and usage of bamboos [13]. However, little is known about the site factors in luencing the clonal growth of P. bambusoides f. shouzhu [3,14]. In view of the signi icantly economical and ecological functions of P. bambusoides f. shouzhu, an explanation of its clonal growth in forest would be helpful in improving the forestation of bamboo forests in the region.…”
Section: Introductionmentioning
confidence: 99%